(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Since the coup led by Fulgencio Batista on March 10, 1952, began a process of readjustment in the Cuban political structure which will culminate in 1959. The roots of the Cuban revolution bom of national dynamic that is articulated in atleast two fronts: one, concerning the formation of political groups in tone insurrectionary art, conceived and organized outside the established political parties in Cuban parliamentary system, and two, the formulation of a new political discourse that justified the creation of avant-garde groups and insurrectionary strategy. Here is, also the origin of the political culture that will define the Castro and revolutionary ideology, long before the emergence of the Cuban communists and their alleged influence on the development of the Cuban revolution and historiography claims supported by the paradigm of Cold War.